(untitled) (Mustansiria Dental Journal, 2019)
Introduction:The pulp polyp (PP), also known as chronic hyperplastic pulpitis or proliferative pulpitis, is a type of inflammatory hyperplasia. It occurs in a vital tooth with a good blood supply when the pulp has been exposed to caries or trauma. Objective: The aim of this study to evaluate different radiographic periapical changes of primary and permanent dentition in clinically detected pulp polyp patients. Materials and Methods: Patients who were clinically diagnosed with pulp polyp were subjected to radiographic examination. Digital intraoral periapical radiographs of 70 patients with pulp polyp were taken. Various periapical changes of primary and permanent dentition in the digital radiographs were recorded . The data obtained was subjected to statistical analysis using SPSS version 16.0. Result: All 70 patients showed definite periapical changes. Out of which periodontal ligament (PDL) space widening was seen in all 70 cases (100%), lamina dura discontinuity was observed in 50 cases (71.43%), periapical rarefying osteitis was noted in 20 cases (28.57%), condensing osteitis was accounted in ten cases (14.29%), periapical granuloma was observed in six cases (8.57%), hypercementosis was accounted in nine cases (12.86%) , root resorption and periapical cyst was observed in eight cases each (11.43%). Conclusions: The results of the present study showed that majority of the pulp polyp patients observed at young age group in both gender and the majority of the pulp polyp patients were associated with definite periapical changes that suggested being a periapical lesion.